Phase, microstructure and service character of as-deposited and short-time heat-treated Ni-Mo alloys with mixed state. - Hong Xu; Ning Li; Qinghua Zhuo; Lirong Lu; Weizeng Chen (PLoS ONE)
Considering the amorphous and nano-crystalline cluster structure and their activity, on the basis of the mixed structure Ni-Mo alloys, the crystallization kinetics of the alloys and the performance of the alloys after heat treatment with different mixed structure were studied. The phase structure and composition were determined by X-ray powder diffraction. The crystallization activation energy of the mixed structure was obtained by differential scanning calorimetry. The electrochemical activity of the mixed structure alloy was determined by electrochemical analysis. The experimental results show that the structural stability of the mixed-structure alloy is better, but the crystallization activation energy is much lower than that of the amorphous alloy. The crystallization process consists of a meta-stable structure transition and a new phase formation. The electrochemical properties of the alloy indicated that the alloy with the mixed structure has higher electrochemical activity, with higher hardness and better corrosion resistance, which results from the large true contact surface and the large number of active centers in this material structure.